Otoritas Teks Sebagai Pusat dari Praktik Umat Islam - Subkhani Kusuma Dewi (Jurnal Living Hadis, 2016)
Anthropologically speaking, interrelation between text and several practices of muslim community in Indonesia (that prove their obedience to the Islamic norms and official doctrine), is in fact heterodox. This premise verifies various elements of the local culture that always interweave and work together in dialogue through rituals and symbols. In shaping this new perspective of Anthropology of Islam, some Islamisists made claim the major tasks of ethnographers to depicts Islam with diverse expressions of meaning, emotion, as well feeling, as practiced by Muslims, whom are the object of authority and the text. This point of view shows the importance of the study of the texts in a broader ethnographic process. The role of the latter study is to strengthen the cultural anthropology of the Muslim community and at the same time discover the power and authority of the text as an interpretive resources and practices for muslim communities.